1998
DOI: 10.1063/1.122543
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic wet chemical etching of GaN

Abstract: We demonstrate well-controlled crystallographic etching of wurtzite GaN grown on c-plane sapphire using H 3 PO 4 , molten KOH, KOH dissolved in ethylene glycol, and NaOH dissolved in ethylene glycol between 90 and 180°C, with etch rates as high as 3.2 m/min. The crystallographic GaN etch planes are ͕0001͖, ͕1010͖, ͕101 1͖, ͕101 2͖, and ͕1013͖. The vertical ͕1010͖ planes appear perfectly smooth when viewed with a field-effect scanning electron microscope. The activation energy is 21 kcal/mol, indicative of reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
152
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(183 citation statements)
references
References 18 publications
13
152
1
1
Order By: Relevance
“…These films are degenerately ntype (~ 10 20 cm -3 ) due to residual defects or impurities. Ti metal contacts were patterned by liftoff on the periphery of the samples, and etching performed in a standard electrochemical cell consisting of a teflon sample holder and a Pt wire cathode [2][3][4][5][6][9][10][11][12][13][14]. An unfiltered 450W Hg arc lamp ~ 15cm from the sample provided illumination of the samples, which were immersed in unstirred KOH, NaOH or H 2 O/AZ400K solutions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These films are degenerately ntype (~ 10 20 cm -3 ) due to residual defects or impurities. Ti metal contacts were patterned by liftoff on the periphery of the samples, and etching performed in a standard electrochemical cell consisting of a teflon sample holder and a Pt wire cathode [2][3][4][5][6][9][10][11][12][13][14]. An unfiltered 450W Hg arc lamp ~ 15cm from the sample provided illumination of the samples, which were immersed in unstirred KOH, NaOH or H 2 O/AZ400K solutions.…”
Section: Methodsmentioning
confidence: 99%
“…Molten KOH and elevated temperature H 3 PO 4 can produce etch pits on GaN [2,3]. Recently hot solutions (90-180ºC) of KOH or NaOH in ethylene glycol and KOH or H 3 PO 4 at similar temperatures have been used to produce well-defined crystallographic etching of wurtzite GaN after initial formation of mesas by dry etching [4]. If the GaN nearsurface region has been damaged by processes such as dry etching or high temperature annealing, H 3 PO 4 , NaOH or KOH solutions have been found to remove the N 2 -deficient material and stop at the underlying undamaged GaN [5].…”
Section: Introductionmentioning
confidence: 99%
“…We used in our study two well-known wet etchants suitable for GaN, KOH [20] and TMAH [21]. TMAH has shown more reduction in the waveguide sidewall roughness as compared to that observed with KOH.…”
Section: Wet-chemical Post-processing and Surface Roughness Measurementsmentioning
confidence: 99%
“…In Palacios et al's report [87], using kali hydroxide (KOH) at 80 o C, etching was only observed on the N-face and not the Ga-face. Nowaday, phosphoric acid (H 3 PO 4 ) [88], [89] is the most commonly used etchant in GaN device fabrication. The H 3 PO 4 etching process is often carried out at the high temperatures (~190 o C) with a etching rate varying in the range of 0.013 -3.2 µm/min [88].…”
Section: Basic Propertiesmentioning
confidence: 99%